Economic, Financial, Social and Religious Lessons from History for the Post Pandemic World - Dr. Muhammad Riaz Mahmood; Dr. MuzammilKhurshid; Muhammad Irfan Ahmad; Dr. Ihsanur Rahman Ghauri (Elementary Education Online, 2023)
The objective of this analytical and descriptive study is to serve the post-pandemic world by exploring the economic, financial and religious lessons derived from history.Pandemics havedisturbed humanity at differenttimes.The coronavirus, like all previous epidemics, has damaged humans to an alarming extent.During the awful stages of the pandemic, humanity pondered over all the circumstances. As a result of this purposefulthinking, severalprecious lessons have come to light in the field of economy and religion.An impartial analysis of thesebeneficial lessons has been presented in this research article.